ANALISIS PSIKOLOGIS TERHADAP PENYEBAB TINDAKAN KRIMINAL - Zahra Permata Sari; Nadia Karin; Artika Cesar Aura Devi; Ajeng Cahya Lestari; Tugimin Supriyadi (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2025)
Crime is a social phenomenon that is increasingly worrying because it is no longer considered merely a deviation from norms, but has developed into a subculture of society. This study aims to examine crime from a psychological perspective by examining internal and external factors that influence criminal behavior. The method used is a literature study by collecting and analyzing various relevant scientific sources. In conclusion, the psychological approach makes an important contribution to understanding and repeating criminal behavior holistically and in a scientific manner.